An analysis of animal healthcare service delivery in Kenya - Ndung'u, Leah; Oruko, Leonard (International Food Policy Research Institute, 2009)
One important objective of agricultural polices and interventions in developing countries is to commercialize and intensify agricultural production. As argued in Chapter 5, to intensify their agricultural production, smallholder households may require access to a range of support services, including improved seeds, inorganic fertilizers, credit, technical advice, market information, and linkages to output markets. In this case study one of the critical inputs for animal production— animal healthcare services—is analyzed. The control of animal diseases and the promotion and protection of animal health through efficient and reliable animal healthcare services are essential components of any effective animal breeding and production program and constitute an essential prerequisite to livestock development. Despite remarkable technical advances in the diagnosis, prevention, and control of animal diseases, the condition of animal health throughout the developing world remains generally poor, causing substantial economic losses and hindering any improvement in livestock productivity.